Achieving Exceptional Photocatalytic Activity and Selectivity through a Well‐Controlled Short‐Ordered Structure: A Case Study of NaxTaOy⋅n H2O. Issue 16 (2nd July 2015) - Su, Yiguo; Lang, Junyu; Du, Chunfang; Bian, Fenggang; Wang, Xiaojing
Abstract The present work reports the preparation of a short‐ordered NaxTaOy⋅n H2O catalyst that exhibits exceptional and highly efficient photocatalytic reactivity toward aerobic oxidation relative to its crystalline counterpart. Synchrotron radiation wide‐angle X‐ray scattering and transmission electron microscopy results indicated that the as‐synthesized catalyst shows short‐ordered features with well‐controlled short‐range ordering limits and defect chemistry. The short‐ordered structure of NaxTaOy⋅n H2O predicted large amounts of defective centers and high surface areas that may play critical roles in visible‐light harvesting and photocatalytic aerobic oxidation. This work may provide a novel strategy for the development of short‐ordered catalytic systems with well‐controlled defect chemistry that exhibit highly efficient photocatalytic properties.